2004
DOI: 10.1159/000080204
|View full text |Cite
|
Sign up to set email alerts
|

Role of Contrast CT in Acute Lower Gastrointestinal Bleeding

Abstract: Objective: To evaluate the role of CT abdomen in the localization of acute lower gastrointestinal bleeding. Summary Background Data: The source of bleed in acute lower gastrointestinal bleeding is often difficult to localize. The role of CT in the evaluation of this group of patients has not been clearly addressed. Methods: A retrospective review of all patients with acute lower gastrointestinal bleeding over a 3-year period was carried out. When endoscopy failed to localize the source and bleeding continued, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
0
22
0
1
Order By: Relevance
“…In fact, recent studies have suggested a good performance for the detection of sources of GI bleeding using CT. However, reports about the usefulness of CT in evaluating lower GI bleeding so far have been limited in number and scope [5][6][7][8][9], and studies on the utility of CT for the evaluation of patients with upper GI bleeding are mostly restricted to a few anecdotal reports [10,11]. In addition, CT protocols vary considerably across the different studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, recent studies have suggested a good performance for the detection of sources of GI bleeding using CT. However, reports about the usefulness of CT in evaluating lower GI bleeding so far have been limited in number and scope [5][6][7][8][9], and studies on the utility of CT for the evaluation of patients with upper GI bleeding are mostly restricted to a few anecdotal reports [10,11]. In addition, CT protocols vary considerably across the different studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CT protocols vary considerably across the different studies. Some investigators used water as oral contrast media (CM) [6] whereas other administered oral iodinated CM [7]. Some authors performed unenhanced and arterial phase CT imaging [4][5][6] whereas others have shown good conspicuity for bleeding source detection with CT after intra-arterial injection of CM with an angiography catheter placed in the celiac trunc [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of vascular lesions affecting the colon is unknown. The colonic vascular malformations are detected only when the child presents with LGI bleed [3]. The clinical workup is followed up with angiography, blood pool scan, magnetic resonance imaging, doppler studies and endo-sonography.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low negative predictive value of the Meckel's scan suggests that exploratory laparotomy or laparoscopy may be indicated instead of scintigraphic scanning in the assessment of the anemic (hemoglobin less than 11g/dL) pediatric patient with lower GI bleeding, especially in those with a high suspicion of Meckel's diverticulum bleed [5]. Computed tomography is useful in diagnosis of acute lower gastrointestinal bleeding where endoscopy fails to localize the lesion and bleeding has stopped temporarily [3]. In obscure GI bleed where the lesion cannot be localized the capsule endoscopy has a high diagnostic yield [6].…”
Section: Lower Gastrointestinal Vascular Malformation In Childrenmentioning
confidence: 99%